Effect of additional oat supplementation in forage based feeding during gestation and lactation periods on ewe body condition, performance, blood glycose and β-hydroxybutyrate concentration in organic farm - Peep Piirsalu; Tanel Kaart; Jaak Samarütel; Silvi Tölp; Aire Ilves; Hanno Jaakson; Irje Nutt (Agraarteadus, 2019)

(untitled)
The aim of this study was to estimate the feeding strategies of pregnant and lactating ewes fed only silage/hay or supplemented with concentrates (oat) on the ewe body condition score (BCS), production of ewes (lambs born per ewe lambed (LB), lambs born alive per ewe lambed (LBA), lambs born dead per ewe lambed (LBD), lamb birth weight (LBW), lamb 100 day weight (L100DW)) and ewe blood glycose and β-hydroxybutyrate (BHB) concentrations. The Estonian White Face and Texel ewes (107 ewes) were divided into two similar groups: the experimental group (59 ewes) and control group (48 ewes). For 45–60 days before lambing (from 90th–105th day of gestation) the experimental ewes were fed in addition to forage feeds (silage, hay or pasture grass) 0.22 kg of organic oat per day (totally 10 kg in gestation period) and 0.3 kg of oat during suckling period (totally 13.5 kg per ewe). The control group of ewes were fed only with forage-based rations (silage, hay, pasture grass) without cereals. Ewe BCS was assessed before mating, on 130–140 day of pregnancy, after lambing (following 7th–10th day), during the 2nd suckling months (45–60 suckling day) and at weaning of lambs by two observers during the whole study. It was concluded that additional feeding of minimal amount of oats increased the ewes BCS in the experimental group at 130–140 day of pregnancy (BCS was respectively 3.36 and 2.97, p < 0.001) and on the 45–60th suckling day (BCS respectively 2.84 and 2.52, p < 0.001) compared with control ewes, but did not affect BCS of ewes at the end of the experiment (at weaning). Production traits (LBA, LBW, L100DW) nor ewes blood glycose and β-hydroxybutyrate (BHB) concentrations at the 130–140 days of pregnancy and 7–10 days after lambing were not affected by supplementation of oat to ewes' diet